Agricultura Sostenible Adaptada al Clima (ASAC): Alternativas para el Corredor Seco en Guatemala - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Center for Tropical Agriculture; Ministerio de Agricultura Ganadería y Alimentación (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The present document seeks that farmers, extensionists and any organization linked to the agricultural sector, with an interest in implementing, promoting or investing in CSA prioritized practices, broaden its vision and have a benchmark so that, beyond knowing the technical aspects for its implementation, can explore the barriers and opportunities associated with its implementation, the economic, social and environmental costs and benefits that can be generated in the short and long term, as well as other practices with which it could have synergistic effects in productivity, adaptation and mitigation.